2015
DOI: 10.17116/otorino201580643-45
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis of chronic adenoiditis in the children

Abstract: This study was undertaken with the purpose of improving the effectiveness of the preventive treatment of chronic adenoiditis in the children. The open randomized comparative study included 219 children aged from 6 to 7 years presenting with clinical and anamnestic signs of chronic adenoiditis. The study group was comprised of 113 patients given the Streptococcus salivarius K12-based probiotic complex during 30 days in combination with the nasal-douche. The control group consisted of 106 patients treated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that treatment with oropharyngeal probiotic reduced the exacerbation frequency of chronic adenoiditis and the requirement for medication ( 43 ). A similar beneficial effect of oropharyngeal complementary treatment was observed in our study, during intervention period; when acute respiratory symptoms onset, children complementary treated with oropharyngeal ENT-K12 in combination with medication (3 courses in total; 1 took antibiotics for 1 day and 2 took antiviral drugs for 1 and 2 days, respectively) or without medication further shortened the duration of respiratory symptoms onset compared to those treated with only medication in control group (14 courses in total; prescribed with antibiotics, antiviral drugs or antipyretics for various period of time from 1 to 10 days).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that treatment with oropharyngeal probiotic reduced the exacerbation frequency of chronic adenoiditis and the requirement for medication ( 43 ). A similar beneficial effect of oropharyngeal complementary treatment was observed in our study, during intervention period; when acute respiratory symptoms onset, children complementary treated with oropharyngeal ENT-K12 in combination with medication (3 courses in total; 1 took antibiotics for 1 day and 2 took antiviral drugs for 1 and 2 days, respectively) or without medication further shortened the duration of respiratory symptoms onset compared to those treated with only medication in control group (14 courses in total; prescribed with antibiotics, antiviral drugs or antipyretics for various period of time from 1 to 10 days).…”
Section: Discussionmentioning
confidence: 99%
“…For one article, statistical analysis was not reported [34]. We therefore carried out statistical analysis of their reported data using GraphPad QuickCalcs (https://www.graphpad.com/quickcalcs).…”
Section: Discussionmentioning
confidence: 99%
“…One study investigated the use of SsK12 as a prophylactic treatment to protect children with chronic adenoiditis against episodes of exacerbation [34]. This was a noneplacebo-controlled RCT involving 250 children aged 6 to 7 years.…”
Section: Exacerbation Of Chronic Adenoiditismentioning
confidence: 99%
See 2 more Smart Citations